ANALYZING THE IMPACT OF ROADSIDE FEATURES ON INJURY SEVERITY - Sotonye IKIRIKO; Steve EFE; Oludare OWOLABI (Journal of Construction Project Management and Innovation)
The design and implementation of a multimodal transportation system must address the issue of mobility and sustainability with the objective of making transportation safer, better, faster, and more reliable. Roadway safety hardware which has been provided as a countermeasure to reduce the severity of highway crashes may have a contributing effect to injury severities on the highway. This emphasizes the need to evaluate the effects of roadside features on injury severity along rural and urban roadways.  The study examines the effectiveness of roadside hardware in twenty-four (24) counties in the State of Maryland using the vehicular crash data for the years 2016 to 2018. The relationship between accident occurrence and the traffic and control characteristics of roadway was investigated to develop a Multinomial Logit Model to identify the factors determining the severity of vehicle crashes in relation to roadside features. Findings showed that roadside features such as trees may increase the propensity of a fatal and serious injury relative to a property damage.